RETRACTED: The Influence of Product Quality and Service Quality on Customer Satisfaction Dunkin' Donuts South Jakarta - Estela Septianty; Elwisam Elwisam; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the effect of product quality and service quality on customer satisfaction at Dunkin' Donuts South Jakarta. The results of this study using primary data in the form of a questionnaire with descriptive and inferential analysis methods. The population in this study is an unlimited population and the sample of this study were 100 respondents. The results of the study state that product quality has a significant and positive effect on customer satisfaction. Service quality has a significant and positive effect on customer satisfaction. Product quality and service have a significant and positive effect on customer satisfaction.